2022
DOI: 10.1093/infdis/jiac153
|View full text |Cite
|
Sign up to set email alerts
|

Hamsters Protected from SARS-CoV-2 Delta Variant Challenge after Two Doses of Adjuvanted SARS-CoV-2 Recombinant Spike Protein (S-2P) and One Dose of Beta S-2P

Abstract: SARS-CoV-2 Variants of Concern (VoCs) negatively impact the effectiveness of vaccines. In this study, we challenge hamsters with the Delta variant after two- or three-dose inoculations with SARS-CoV-2 vaccines constructed from stabilized prefusion spike proteins (S-2P) of Wuhan (W) and Beta (B) variants. Compared to three doses of W S-2P, two doses of W S-2P followed by a third dose of B S-2P induced the highest neutralizing antibody titer against live SARS-CoV-2 virus and enhanced neutralization of Omicron va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The neutralizing antibody titre was defined as the reciprocal of the highest dilution capable of neutralising 50% of the infection (NT 50 ) calculated using the Reed-Muench method. Anti-SARS-CoV-2 spike immunoglobulin (IgG) levels were measured by enzyme-linked immunosorbent assay (ELISA) using custom-made 96-well plates coated with S-2P antigen [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neutralizing antibody titre was defined as the reciprocal of the highest dilution capable of neutralising 50% of the infection (NT 50 ) calculated using the Reed-Muench method. Anti-SARS-CoV-2 spike immunoglobulin (IgG) levels were measured by enzyme-linked immunosorbent assay (ELISA) using custom-made 96-well plates coated with S-2P antigen [10].…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that three doses of MVC-COV1901 can improve neutralising antibody response against live SARS-CoV-2 and Omicron variant pseudovirus [9]. We first demonstrated the ability of the Beta variant version of S-2P to protect hamsters from the Delta variant challenge and have also shown improved neutralising antibody levels against a broad spectrum of variants, including the current Omicron variant [10]. In the current study, two groups of participants who have received either two or three doses of MVC-COV1901 were administered with a booster dose of either original MVC-COV1901 or MVC-COV1901 based on the Beta variant in two different dose levels (MVC-COV1901-Beta).…”
Section: Introductionmentioning
confidence: 99%
“…MVC-COV1901 is a subunit COVID-19 vaccine based on the stable prefusion spike protein S-2P of the ancestral SARS-CoV-2 and adjuvanted with CpG 1018 and aluminum hydroxide have previously shown that three doses of MVC-COV1901 can improve the neutralizing antibody response against live SARS-CoV-2 and Omicron variant pseudoviruses [ 10 ]. The current study builds on the observation that the Beta variant version of S-2P protected hamsters from the Delta variant challenge and improved neutralizing antibody levels against the Omicron variant [ 11 ]. For this study, two groups of participants who have received either two or three doses of MVC-COV1901 were administered a booster dose of either original MVC-COV1901 or MVC-COV1901 based on the Beta variant in two different dose levels (MVC-COV1901-Beta).…”
Section: Introductionmentioning
confidence: 99%
“…Viral RNA is readily detectable in the respiratory tract and other tissues (e.g., in the small intestine), which may be useful for evaluating therapeutics and vaccines [ 5 ]. Because studies in hamsters can be completed quickly and in a cost-effective manner, there is an increasing interest in the use of hamsters for accessing vaccines [ 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%